Gestão estratégica de micro e pequenas empresas no mercado regulamentado de farmácias de manipulação - Resende, Marcello Rosa de (2013)
The main goal of this research was to analyze the understanding of regulated environment by owner-managers influence the strategic management of micro and small enterprises of the compounding pharmacies segment. Addressed the strategic management from the perspective of the vision named by Mintzberg, Ahlstrand and Lambel (2000) of entrepreneurial school , witch takes the vision as the foundation of strategic thinking in business. The study was conducted in an area with a special lack of studies related to the subjected, even more so that they understand the different facets of the theme for enterprises operating in a highly regulated environment. The theoretical framework discussed in the context of micro and small enterprises, the strategic management process and the role of owner-managers of the compounding pharmacies segment in Brazil and brought considerations about environment regulation. This research used a qualitativr approach. The research was exploratory and used the multiple case study. The study sample was characterized as a theoretical and intentional and interviews were semi-structured. We identified six types of influence understanding of market regulation by owner-managers and found the answers in the context of strategic management. The results of this research were limited to the sample.